REDUCED PERFUSION ON NITRATE ENHANCED STUDY COMPARED TO RESTING WITH 99mTc-SESTAMIBI IMAGING FOR MYOCARDIAL VIABILITY - Jielani, Asif; Riaz, Mausab; Anees, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Patients with ischemic heart disease and left ventricular dysfunction need evaluation for myocardial viability. Two cases of myocardial perfusion imaging for viability study are discussed. Viability imaging is performed with 99mTc-Sestamibi (99mTc-MIBI), acquiring images with and without nitrate enhancement. Improvement in perfusion in nitrate enhanced images is suggestive of myocardial viability. In these cases, there was paradox effect showing reduced uptake on nitrate enhanced images than on resting images. Technical factors of equal radiotracer dose in both studies, pre-imaging time and processing were considered. Since no such contributing factor was delineated, it is postulated that phenomena can occur due to differential effects of oral glyceryl triglyceryl trinitrate (GTN) on normal and diseased vessels. Keywords: Myocardial viability, Glyceryl trinitrate,99mTc-Sestamibi, Radiotracers